Patient with progressive chest pain and dyspnea after aortic valve replacement - Ozair Rizvi; Sarab Sodhi; Joshua S. Rempell (Journal of the American College of Emergency Physicians Open)
Abstract A 45‐year‐old man presented to the emergency department (ED) with progressive chest pain and dyspnea 3 months after aortic valve replacement. He had been evaluated by his primary care physician and cardiologist and no diagnosis had been made. On arrival, the emergency physicians performed point‐of‐care ultrasonography, which showed a large hypoechoic collection compressing the right ventricle. This prompted further workup, including a computed tomography of the chest, which revealed a large fluid collection in the anterior mediastinum. Subsequently, cardiothoracic surgery was consulted and the patient was taken to the operating room for a sternal washout with evacuation of the collection.